An Inventory of Brick Kilns in Kanpur Dehat District - Sanyal, Srabani; Niranjan, Divanshu S. S. (National Geographical Journal of India, 2022)
Urbanization in India is characterized by unplanned and uncontrolled growth leading to urban sprawl. As a result there is an increase in the demand of infrastructural facilities such as housing, transport and communication which requires large quantities of constructional materials such as bricks. Brick making is a traditional industry but has emerged as an important activity. India is the second largest producer of clay bricks in the world after China with an estimated brick production of around 140 billion bricks per year from nearly 50,000 small/ cottage scale brick kilns distributed throughout India. There are 3.5 million workers employed in this sector. For manufacturing bricks at least 2.4 hectares of land is required; 0.8 hectares for the brick kilns itself and 1.6 hectares for digging out 0.9 meters of topsoil. Brick making has directly or indirectly caused environmental and health problems. The present study tries to investigate the distribution of brick kilns in Kanpur Dehat district in India and examine the type of workforce engaged in brick kilns in the study area.